Emissão de dívida corporativa no exterior: um experimento quase-natural no Brasil - Gabrielli, Marcio Fernandes (2018)
This paper analyzes the reasons that lead Brazilian companies to issue debt securities in the international market. For this purpose, the law that established the taxation on foreign exchange derivatives (announced on 07/26/2011, implemented on 09/16/2011 and revoked on 06/12/2013), in force during the period of the then Minister of Fazenda Guido Mantega, was used as a quasi-natural event to analyze whether the probability of issuance in the international market is affected by a governmental measure. A reduction in the probability of issuance of bonds by Brazilian companies in the international market during the period of the law was observed, while an increase in this probability for domestic issues was observed, suggesting a substitution effect. This effect would be related to the fact that the taxation of foreign exchange derivatives would have generated a break in the covered interest rate parity, since the cost of issuance in the domestic market would have been lower than the cost of issuance in the international market after computing the hedge cost of the foreign exchange risk. This effect was more clearly evidenced by the fact that it affected in a different way companies with different foreign exchange exposures. Net exporting companies, for which the foreign exchange debt would function as a natural hedge of their operations, were less affected than net importing companies, which would need to hedge their foreign exchange debts in order not to incur in a larger foreign exchange exposure. In this way, there were evidences that companies act in the direction of raising funds in the market that allows them the lowest final funding cost, seeking 'windows of opportunity' between local and international markets – already incorporating the foreign exchange hedge cost – in order to decide in which market to issue their debt securities. These results also make it possible to argue that the government was able to influence corporate internal financing decision – debt issuance in domestic or international markets – as well as affect its funding costs and hence its cost of capital.